2019
DOI: 10.1111/1346-8138.15034
|View full text |Cite
|
Sign up to set email alerts
|

Coinheritance of generalized pustular psoriasis and familial Behçet‐like autoinflammatory syndrome with variants in IL36RN and TNFAIP3 in the heterozygous state

Abstract: Generalized pustular psoriasis (GPP) is now known to be caused by biallelic variants in IL36RN and monoallelic variants in CARD14 and AP1S3. The presence of a modifier locus or oligogenic inheritance have been hypothesized. We report on a patient with a unique coinheritance of pathogenic variants in IL36RN (c.115+6T>C) and TNFAIP3 (c.547C>T, p.R183*) causing the genetic entities GPP and familial Behçet‐like autoinflammatory syndrome (AISBL). The heterozygous variant in IL36RN identified by Sanger sequencing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Psychosomatic and hereditary factors have been suggested to have a role in the etiology of geographic tongue. Liang et al (2019) reported that biopsies revealed similarities among geographic tongue patients with different genotypes with the neutrophils prominently infiltrating the epidermis and the expression ratio of IL‐36Ra/IL‐36γ in lesioned tongues with individuals harboring different genotypes decreased significantly compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosomatic and hereditary factors have been suggested to have a role in the etiology of geographic tongue. Liang et al (2019) reported that biopsies revealed similarities among geographic tongue patients with different genotypes with the neutrophils prominently infiltrating the epidermis and the expression ratio of IL‐36Ra/IL‐36γ in lesioned tongues with individuals harboring different genotypes decreased significantly compared with controls.…”
Section: Discussionmentioning
confidence: 99%